The effects of sedentary behaviour interventions on work-related productivity and performance outcomes in real and simulated office work: A systematic review. (February 2019) - Sui, Wuyou; Smith, Siobhan T.; Fagan, Matthew J.; Rollo, Scott; Prapavessis, Harry
Abstract: This review examined the impact of environmental, behavioral, and combined interventions to reduce occupational sedentary behaviour on work performance and productivity outcomes. Productivity outcomes were defined as variables assessing work-related tasks (e.g., typing, mouse), whereas performance outcomes were categorized as any variables assessing cognition that did not mimic work-related tasks. Nine databases were searched for articles published up to January 2018. Sixty-three studies were identified that met the inclusion criteria: 45 examined a productivity outcome (i.e., typing, mouse, work-related tasks, and absenteeism), 38 examined a performance outcome (i.e., memory, reading comprehension, mathematics, executive function, creativity, psychomotor function, and psychobiological factors), and 30 examined a self-reported productivity/performance outcome (i.e., presenteeism or other self-reported outcome). Overall, standing interventions do not appear to impact productivity/performance outcomes, whereas walking and cycling interventions demonstrate mixed null/negative associations for productivity outcomes. Hence, standing interventions to reduce occupational sedentary behaviour could be implemented without negatively impacting productivity/performance outcomes. Highlights: Occupational sedentary interventions do not appear to impact work performance. Standing interventions do not appear to impact work performance/productivity. Walking and cycling interventions may negatively affect some productivity outcomes.